Measurements of the neutron spectrum in transit to Mars on the Mars Science Laboratory. (April 2015) - Köhler, J.; Ehresmann, B.; Zeitlin, C.; Wimmer-Schweingruber, R.F.; Hassler, D.M.; Reitz, G.; Brinza, D.E.; Appel, J.; Böttcher, S.; Böhm, E.; Burmeister, S.; Guo, J.; et al.
Abstract: The Mars Science Laboratory spacecraft, containing the Curiosity rover, was launched to Mars on 26 November 2011. Although designed for measuring the radiation on the surface of Mars, the Radiation Assessment Detector (RAD) measured the radiation environment inside the spacecraft during most of the 253-day, 560-million-kilometer cruise to Mars. An important factor for determining the biological impact of the radiation environment inside the spacecraft is the specific contribution of neutrons with their high biological effectiveness. We apply an inversion method (based on a maximum-likelihood estimation) to calculate the neutron and gamma spectra from the RAD neutral particle measurements. The measured neutron spectrum (12–436 MeV) translates into a radiation dose rate of 3.8 ± 1.2 μGy / day and a dose equivalent of 19 ± 5 μSv / day . Extrapolating the measured spectrum (0.1–1000 MeV), we find that the total neutron-induced dose rate is 6 ± 2 μGy / day and the dose equivalent rate is 30 ± 10 μSv / day . For a 360 day round-trip from Earth to Mars with comparable shielding, this translates into a neutron induced dose equivalent of about 11 ± 4 mSv.